Analysis, Stability and Distribution of Pharmaceuticals and Drugs of Abuse over a Period of One Year in Formalin-Fixed Liver and Formalin Solutions. Issue 2 (12th August 2022) - Orfanidis, Amvrosios; Gika, Helen; Theodoridis, Georgios; Chatziioannou, Anastasia Chrysovalantou; Raikos, Nikolaos
Abstract: The present study reports a thorough research on the stability of drugs of abuse and pharmaceuticals over a time period of 12 months. Fixed-liver tissues and formalin solutions where the tissues were preserved were analyzed using an ultra high performance liquid chromatography--tandem mass spectrometry method that has been developed and validated for this purpose. The method monitors 84 drugs in a 13-minute run. The concentrations of the drugs found were compared with their concentrations determined in the fresh liver tissues in a previous study. In the study, 14 cases with forensic interest were included with the main objective of the analysis and the study of the stability and the distribution of drugs of abuse and pharmaceuticals in the human liver and the formalin solution during preservation. The results showed that the number of detected compounds in the first month was significantly lower than the compounds found in fresh tissues. The effect of formalin was catalytic, and few substances could be detected. Specifically, out of the 86 positive detections of the monitored substances in the fresh tissues (in which 25 different substances were found), only 32 (37%) remained detectable 3 months after, 20 (23%) 6 months after and 15 (17%) 12 months after.